(untitled) (CIPEEX, 2022)
VIOLENCE IS A PROBLEM THAT HAS PLAGUED BRAZIL FOR DECADES. AMONG THEM IS POLICEVIOLENCE STEMMING FROM ARBITRARY CONDUCT IN APPROACHES THAT OFTEN END UP RESULTING IN DEATH.IN 2021 MORE THAN SIX THOUSAND PEOPLE WERE KILLED BY CIVILIAN AND MILITARY POLICE OFFICERS IN THECOUNTRY, THAT IS, AN AVERAGE OF 17 CIVILIAN DEATHS CAUSED BY POLICE OFFICERS PER DAY IN BRAZIL(USP, 2021). IN VIEW OF THE POSSIBLE UNPREPAREDNESS OF POLICE OFFICERS, A WAVE OF DISTRUST WASCREATED AMONG THE POPULATION THAT INSTEAD OF FEELING SAFE WITH THE PRESENCE OF THE POLICE,STARTED TO CREATE AVERSION, ACCORDING TO DATA RELEASED BY IPEA (2010), WHERE ¼ OF BRAZILIANSDO NOT TRUST THE CIVIL AND MILITARY POLICE, AND MORE RECENTLY, DATA RELEASED BY DATAFOLHA (2019),51% OF BRAZILIANS HAVE MORE FEAR THAN TRUST IN THE POLICE FORCES, 41% HAVE MORE TRUST THANFEAR, AND 2% DO NOT KNOW HOW TO ANSWER. GIVEN THE SUBJECT IN QUESTION, THIS PAPER AIMS TOANALYZE LAW 13.869/19, CONSIDERED AS THE LAW OF ABUSE OF AUTHORITY, IN VIEW OF THE FACTUALASPECTS OF POLICE APPROACH IN THE EASTERN REGION OF GOINIA (BRASIL, 2022). SEEKING TOREACH THE EXPECTED RESULTS, THE WORK WAS DIVIDED INTO STAGES. IN A FIRST MOMENT, IT IS INTENDEDTO APPROACH THE LEGALITY OF POLICE APPROACHES, ACCORDING TO THE LEGAL PROVISION AND THESTANDARD OPERATING PROCEDURE (SOP); THEN A FIELD RESEARCH WILL BE DONE, WITH APPLICATION OFQUESTIONNAIRES, IN ORDER TO INVESTIGATE THE PERCEPTION OF THE POPULATION LIVING IN THE EASTREGION OF GOINIA IN RELATION TO POLICE APPROACHES; FINALLY, THE WORK WILL ANALYZE THE LEGALCONSEQUENCES OF THE ACTS OF ABUSE AND EXCESS OF AUTHORITY IN POLICE APPROACHES, POINTING OUTTHE LEGAL MEANS APPLICABLE IN SIMILAR SITUATIONS. THE WORK WILL USE THE QUALI-QUANTITATIVERESEARCH METHOD, FIELD, DOCUMENTARY, EXPLORATORY, AND EXPLANATORY, SEEKING TO COLLECT ANDANALYZE DATA THAT CAN PROVIDE A FEEDBACK TO SOCIETY. IT IS CONSIDERED IMPORTANT TO DISCUSS THETHEME, FOR THE KNOWLEDGE AND FEASIBILITY OF THE FUNDAMENTAL RIGHTS AND GUARANTEES OF THECITIZEN ARE NON-NEGOTIABLE AND CONSIDERED DEFENSE INSTRUMENTS TO BE INVOKED IN THEIMMINENCE OR VIOLATION OF RIGHTS. ACCORDING TO PREVIOUS DATA COLLECTED, IT WAS OBSERVED THAT INTHE EASTERN REGION OF GOINIA, THERE ARE MANY COMPLAINTS ABOUT POSSIBLE ABUSES ANDEXCESSES OF POWER BY POLICE AUTHORITIES WHEN APPROACHING CITIZENS. HOWEVER, THE POLICEAPPROACH SYMBOLIZES AN ADMINISTRATIVE ACT, AND THE LEGALITY OF THE POLICE APPROACH IS REGULATEDIN SEVERAL BRANCHES OF BRAZILIAN LAW. FOCUSING ON FUNDAMENTAL RIGHTS AND GUARANTEES AND ONTHE DIGNITY OF THE HUMAN PERSON, THE PAPER WILL HIGHLIGHT THE CONSTITUTIONAL ASPECTS OF THE LEGAL CONSEQUENCES OF EXCESS AND ABUSE OF POLICE AUTHORITY WHEN BEING APPROACHED. THUS,FUNDAMENTAL RIGHTS AND GUARANTEES GUIDE POLICE ACTIVITY, AND AS A CONSEQUENCE, THEY ARE THEBASIS FOR A FAIR PERFORMANCE, IN ACCORDANCE WITH THE DIGNITY OF THE HUMAN PERSON AND STRICTLYFOLLOWING WHAT THE LEGISLATION IN FORCE MANDATES.